BOLALAR DUNYOQARASHINI SHAKLLANTIRISHDA “BOLAJON” TELEKANALINING O‘RNI VA AHAMIYATI - Oripova, N.X.; Ashirova, S.B. (SCIENCE and SOCIETY, 2019)
The article outlines the role and importance of television in shaping the outlook of children. In addition, the article analyzes the programs of the “Bolojon ” TV channel, loved by children, and outlines their capabilities in satisfying the spiritual challenges of the children of the current period.